2020
DOI: 10.3390/coatings10090859
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Evaluation of Thermal Barrier Coatings Interface Delamination Using Terahertz Technique Combined with SWT-PCA-GA-BP Algorithm

Abstract: Thermal barrier coatings (TBCs) are usually subjected to the combined action of compressive stress, tensile stress, and bending shear stress, resulting in the interfacial delamination of TBCs, and finally causing the ceramic top coat to peel off. Hence, it is vital to detect the early-stage subcritical delamination cracks. In this study, a novel hybrid artificial neural network combined with the terahertz nondestructive technology was presented to predict the thickness of interface delamination in the early st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…(1) Based on the characteristics of the controlled system parameters, determine the basic structure of the BP neural network, including the number of input nodes [8], hidden layer nodes, and output nodes. Initialize the weighting coefficients w 1 ij(0) and w 2 ij(0) with initial values.…”
Section: Bp Neural Network Pid Controlmentioning
confidence: 99%
“…(1) Based on the characteristics of the controlled system parameters, determine the basic structure of the BP neural network, including the number of input nodes [8], hidden layer nodes, and output nodes. Initialize the weighting coefficients w 1 ij(0) and w 2 ij(0) with initial values.…”
Section: Bp Neural Network Pid Controlmentioning
confidence: 99%
“…Existing information indicated that machine learning was highly advantageous in large-scale data modeling [26][27][28]. Therefore, machine learning was introduced to process terahertz time-domain spectral data in this study.…”
Section: Algorithms and Modelsmentioning
confidence: 99%
“…Existing information has shown that machine learning has been better applied in evaluating and predicting performance [26][27][28]. In this study, a simulation model was constructed based on the microstructural characterization data obtained from the inspection of actual service blades.…”
Section: Introductionmentioning
confidence: 99%
“…The data must be uniformly planned to ensure the validity of the data. Normalization methods are usually used for data preprocessing [26,27]. The formulation of the BP model can be expressed as follows:…”
Section: Bp Neural Network Model Optimized By Genetic Algorithmmentioning
confidence: 99%